Estudio de Factibilidad para la Creación de una Caja de Ahorro a los Socios del Sistema de Riego Chiriyacu – Lucero del Cantón Calvas - Rojas Torres, Paola Elizabeth (2017)
The present work of thesis denominated "FEASIBILITY STUDY FOR THE CREATION OF A SAVINGS BOX TO THE PARTNERS OF THE IRRIGATION SYSTEM CHIRIYACU-LUCERO OF CANTÓN CALVAS" aims to contribute with a proposal that seeks the integration of the partners of the irrigation system To financial services, encouraging them to save and developing a source of their own resources to finance their productive activities. Five specific objectives were based on a market, technical, administrative-legal, economic-financial and financial evaluation In order to comply with these objectives, we used some methods such as the scientific that allowed the development of literature review, the inductive method that helped establish the demand, the deductive through which the legal structure was established, the descriptive method that was detailed The processes and requirements for the generation of the service of the cashier, and finally the analytic through which it allowed to analyze the information obtained in the surveys, as well as the results of the financial evaluation indicators. As for the results obtained in the market study, it was demonstrated that there is demand of 209 partners; In the technician it was determined that the center of the parish Lucero is the ideal location for the savings bank, the demand to cover, as well as the necessary requirements and processes; In addition the administrative and legal structure was shaped, in the economic-financial study was determined the investment, financing, costs, income, cash flow, and cash flow to later use the financial assessment tools as net present value (NPV), internal rate of return (IRR), benefit-cost ratio (RBC), period of capital recovery (PRC) and sensitivity analysis. In conclusion, the studies corroborated the feasibility of the savings bank for the partners of the Chiriyacu-Lucero irrigation system, guaranteeing sustainability and generating economic and social development.